Transient L5 Nerve Root Palsy Caused by Subfascial Drain After Lumbar Surgery: Case Report and Literature Review. Issue 2 (18th April 2022) - Barile, Francesca; Ruffilli, Alberto; Viroli, Giovanni; Manzetti, Marco; Traversari, Matteo; Faldini, Cesare
Abstract : Case: We describe the case of a 45-year-old woman who developed a transient L5 deficit after a posterior L4-L5 interbody fusion. A perfusion computed tomography scan ruled out all described causes of postoperative deficit and showed compression of the right L5 root by the subfascial drain. The deficit spontaneously resolved. Conclusion: New neurological deficit after spine surgery is a complication that requires a quick diagnostic and therapeutic approach. This particular case is of interest not only because it describes a rarely reported complication (transient neurological motor deficit after posterior fusion) but also because the hypothesized cause has never been described before.